Effect of inherent innovativeness and consumer readiness on attitudes to mobile banking. Issue 4 (December 2017) - Frimpong, Kwabena; Al-Shuridah, Obaid; Wilson, Alan; Sarpong, Frederick
Abstract Despite the strong evidence that many consumers relish their experience with mobile banking, others indicate that some segments may not be comfortable with these emerging digitized platforms due to certain inherent personal traits. Drawing insights from the socio-psychology and innovation/SSTs adoption literature, this paper tested a structural model with inherent innovativeness as an antecedent variable, and consumers' attitude to M-banking, as a mediator to their future usage intention. The moderating effect of consumer readiness on the hypothesized relationship between consumers' attitudes and intention to use mobile banking was also examined. The model was tested on survey data from 720 respondents from the United Kingdom (UK). Findings show that inherent innovativeness significantly explains attitudes to mobile banking. There were, however, mixed outcomes concerning the effects of three dimensions of consumer readiness on the link between attitudes and intention to use mobile banking. The results show that only ability exerts a positive and a significant effect on the examined relationship. The effects ofmotivation androle clarity seemed insignificant. The findings from this paper can help retail bank managers improve their channel and promotional decisions in order to enhance the service experience of relevant segments.